Brucella suis Vaccine Strain 2 Induces Endoplasmic Reticulum Stress that Affects Intracellular Replication in Goat Trophoblast Cells In vitro - Wang, Xiangguo; Lin, Pengfei; Li, Yang; Xiang, Caixia; Yin, Yanlong; Chen, Zhi; Du, Yue; Zhou, Dong; Jin, Yaping; Wang, Aihua (Frontiers in Cellular and Infection Microbiology, 2016)
Brucella has been reported to impair placental trophoblasts, a cellular target where Brucella efficiently replicates in association with the endoplasmic reticulum (ER), and ultimately trigger abortion in pregnant animals. However, the precise effects of Brucella on trophoblast cells remain unclear. Here, we describe the infection and replication of Brucella suis vaccine strain 2 (B.suis.S2) in goat trophoblast cells (GTCs) and the cellular and molecular responses induced in vitro. Our studies demonstrated that B.suis.S2 was able to infect and proliferate to high titers, hamper the proliferation of GTCs and induce apoptosis due to ER stress. Tunicamycin (Tm), a pharmacological chaperone that strongly mounts ER stress-induced apoptosis, inhibited B.suis.S2 replication in GTCs. In addition, 4 phenyl butyric acid (4-PBA), a pharmacological chaperone that alleviates ER stress-induced apoptosis, significantly enhanced B.suis.S2 replication in GTCs. The Unfolded Protein Response (UPR) chaperone molecule GRP78 also promoted B.suis.S2 proliferation in GTCs by inhibiting ER stress-induced apoptosis. We also discovered that the IRE1 pathway, but not the PERK or ATF6 pathway, was activated in the process. However, decreasing the expression of phosphoIRE1α and IRE1α proteins with Irestatin 9389 (IRE1 antagonist) in GTCs did not affect the proliferation of B.suis.S2. Although GTC implantation was not affected upon B.suis.S2 infection, progesterone secretion was suppressed, and prolactin and estrogen secretion increased; these effects were accompanied by changes in the expression of genes encoding key steroidogenic enzymes. This study systematically explored the mechanisms of abortion in Brucella infection from the viewpoint of pathogen invasion, ER stress and reproductive endocrinology. Our findings may provide new insight for understanding the mechanisms involved in goat abortions caused by Brucella infection.